2009
DOI: 10.1099/vir.0.007971-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a spliced rhesus rhadinovirus gene with homology to the K15 gene of Kaposi's sarcoma-associated herpesvirus

Abstract: Rhesus monkey rhadinovirus (RRV) is a gamma-2 herpesvirus related to the human Kaposi's sarcoma-associated herpesvirus (KSHV or human herpesvirus 8). This study identified an alternatively spliced gene at the right side of the RRV genome (strain 17577) between open reading frame 75 and the terminal repeat region. Of its eight exons, the first seven encoded up to 12 transmembrane domains, whilst the eighth exon encoded a predicted C-terminal cytoplasmic domain. Structurally and positionally, this RRV gene there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We have shown earlier that K15, through its cytoplasmic C terminal domain activates the NFκB pathway [52], [58], [60] and that this involves the NFκB component RelA/p65 (unpublished). To investigate the involvement of the NFκB pathway in K15-induced capillary tube formation, we silenced RelA/p65 using siRNA.…”
Section: Resultsmentioning
confidence: 86%
“…We have shown earlier that K15, through its cytoplasmic C terminal domain activates the NFκB pathway [52], [58], [60] and that this involves the NFκB component RelA/p65 (unpublished). To investigate the involvement of the NFκB pathway in K15-induced capillary tube formation, we silenced RelA/p65 using siRNA.…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies reported that both K15 alleles activate NF-κB and the Ras/MAPK signalling [ 22 25 ]. Microarray studies revealed that K15 upregulates the expression of genes involved in angiogenesis and cell migration [ 22 , 24 , 25 ], including, among others, COX2 and an NFAT-dependent upregulation of DSCR1 [ 17 , 24 , 25 ]. We previously showed that K15 contributes to the increased angiogenic properties of KSHV infected primary endothelial cells in a matrigel-based capillary tube formation assay [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the injection of rhoptry proteins without productive invasion by the parasite (kiss-and-run model) could account for these populations, it was also possible that in vivo these cells were activated by IFN-␥ to destroy intracellular parasites (46,47), giving rise to a subpopulation of cells with a U-I phenotype due to injection of the Cre during invasion and subsequent death of the parasite. To address this possibility, Ai6 mice were treated with control rat IgG antibody or anti-IFN-␥ monoclonal antibody and infected with Pru-Cre-mCherry.…”
Section: Zsgreen1mentioning
confidence: 99%